2019
DOI: 10.3390/molecules24101971
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Acrylamide and Hydroxymethylfurfural in Extruded Products by LC-MS/MS Method

Abstract: The aim of this study was to develop a liquid chromatography/tandem mass spectrometry LC-MS/MS method for the simultaneous determination of acrylamide and hydroxymethylfurfural (HMF) in corn snack products enriched with food industry by-products: brewer’s spent grain (BSG), sugar beet pulp (SBP) and apple pomace (AP). Development of the method included the study of different sources for ionization, different mobile phases, different extraction conditions as well as different methods of sample preparation. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…The influence of temperature on the formation of AA thus seems confirmed, as demonstrated in previous studies [13,49,50]. In addition, Jozinovic et al [51] have recently shown that the moisture content and temperature during extrusion had a greater impact on the formation of AA in relation to screw speed. Recent results revealed that at low temperatures used for the thermal treatment, the amount of AA formed was lower, even if the treatment duration was longer [52].…”
Section: Correlation Between Acrylamide Content and Biscuit Coloursupporting
confidence: 76%
“…The influence of temperature on the formation of AA thus seems confirmed, as demonstrated in previous studies [13,49,50]. In addition, Jozinovic et al [51] have recently shown that the moisture content and temperature during extrusion had a greater impact on the formation of AA in relation to screw speed. Recent results revealed that at low temperatures used for the thermal treatment, the amount of AA formed was lower, even if the treatment duration was longer [52].…”
Section: Correlation Between Acrylamide Content and Biscuit Coloursupporting
confidence: 76%
“…The influence of temperature on the formation of AA thus seems confirmed, as demonstrated in previous studies [13,49,50]. In addition, Jozinovic et al [51] have recently shown that the moisture content and temperature during extrusion had a greater impact on 408 µg kg -1 3303 µg kg -1 1443 µg kg -1 Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 11 July 2019 doi:10.20944/preprints201907.0157.v1…”
Section: Correlation Between Acrylamide Content and Biscuit Coloursupporting
confidence: 69%
“…Thanks to technological development and the use of both industrial and home-cooking techniques, the knowledge of the application of the thermal treatment to achieve specific food qualities, has increased. Numerous studies have shown that thermal treatment changes the physical and chemical structure of food [ 1 , 7 , 8 , 9 , 10 , 11 ]. Moreover, it is believed that not only heating temperature and time are the most important factors in the formation of hazardous compounds in foods.…”
Section: Introductionmentioning
confidence: 99%